Archiving the American West - Sandweiss, Martha A.; Swift, Gabriel; Wright, Brian (2022)
"Archiving the American West (HIS 431), is an experimental course first offered at Princeton in Spring 2021 and again in Spring 2022 by Professor Martha Sandweiss (History), in collaboration with Gabriel Swift, Curator of Western Americana, and Brian Wright, Ph.D Candidate in History. Its goal was to offer students advanced research skills in Western American history, while also introducing them to the history and contemporary politics of archives and special collections. As originally conceived, the undergraduate seminar was to be taught around a large table in Firestone Library’s Special Collections department. Students would (carefully) pass around manuscript materials, transcribing the handwriting together. They’d work together to decode the logic of photographic albums or old account books, and work in teams to find related materials in the collections. The COVID-19 pandemic compelled the class to pivot to an online format, so Princeton University Library staff generously fast-tracked our voluminous digitization requests, and by the first week of class had digitized more than 850 photographs and 2,000 pages of manuscript material for the students’ study." [seld-description]